After the World Trade Center : rethinking New York City - Sorkin, Michael, 1948-2020; Zukin, Sharon (Routledge, 2002)
Essays consider the recovery of lower Manhattan after the destruction of the World Trade Center, looking back on New York's position as a financial and cultural capital and examining the forces that will shape the future of the World Trade Center site.